Chronic Dietary Supplementation of 4% Figs on the Modification of Oxidative Stress in Alzheimer's Disease Transgenic Mouse Model. (19th June 2014) - Subash, Selvaraju; Essa, Musthafa Mohamed; Al-Asmi, Abdullah; Al-Adawi, Samir; Vaishnav, Ragini
Abstract : We assessed the changes in the plasma A β, oxidative stress/antioxidants, and membrane bound enzymes in the cerebral cortex and hippocampus of Alzheimer's disease (AD) transgenic mice (Tg2576) after dietary supplementation of Omani figs fruits for 15 months along with spatial memory and learning test. AD Tg mice on control diet without figs showed significant impairment in spatial learning ability compared to the wild-type mice on same diet and figs fed Tg mice as well. Significant increase in oxidative stress and reduced antioxidant status were observed in AD Tg mice. 4% figs treated AD Tg mice significantly attenuated oxidative damage, as evident by decreased lipid peroxidation and protein carbonyls and restoration of antioxidant status. Altered activities of membrane bound enzymes (Na + K + ATPase and acetylcholinesterase (AChE)) in AD Tg mice brain regions and was restored by figs treatment. Further, figs supplementation might be able to decrease the plasma levels of A β (1–40, 1–42) significantly in Tg mice suggesting a putative delay in the formation of plaques, which might be due to the presence of high natural antioxidants in figs. But this study warrants further extensive investigation to find a novel lead for a therapeutic target for AD from figs.